ISLAMIC COMMUNITY PARTICIPATION IN ENVIRONMENTAL CONSERVATION: A STUDY OF THE GERAKAN PEDULI LINGKUNGAN (GPL) IN PLASTIC WASTE CONTROL IN COASTAL WEST ACEH, INDONESIA - Putra, Bachrum Syah; Taran, Jovial Pally; Sukri, Sukri (Jurnal Al-Ijtimaiyyah, 2026)
This study examines the role of community participation in environmental conservation through the Gerakan Peduli Lingkungan (GPL), a youth-based community movement engaged in plastic waste control in the coastal area of Meureubo Subdistrict, West Aceh Regency, Indonesia. Situated within the framework of Islamic community development, the study analyzes GPL's contributions to coastal environmental management, the level and patterns of community participation, and the barriers encountered in program implementation. A descriptive qualitative approach was employed, with fieldwork conducted in February 2026. Data were collected through in-depth interviews with 11 informants — including GPL administrators, village officials, and local residents — and complemented by direct field observations. The findings reveal that GPL contributes through beach clean-up activities, environmental education and awareness campaigns, social media outreach, and community economic empowerment via the productive utilization of plastic waste. Community participation was found to be relatively strong, though unevenly distributed across different social groups, with the main barriers including limited public awareness, inadequate facilities and infrastructure, and insufficient financial support. The novelty of this study lies in its analysis of a community-based environmental movement in a coastal Muslim-majority setting as an integrated model of social welfare and sustainable development, combining social, educational, communicative, and economic approaches rooted in collective community action. The findings offer practical implications for local governments and community organizations in strengthening participatory waste governance, while enriching theoretical discussions on Islamic community development and grassroots environmental stewardship.